2015
DOI: 10.1007/s10620-015-3684-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased PD-1/PD-L1 Expression Is Associated with the Reduction in Mucosal Immunoglobulin A in Mice with Intestinal Ischemia Reperfusion

Abstract: Intestinal I/R inhibits PD-1/PD-L1 expression on PP CD4(+) T cells, which was associated with an impaired intestinal immune system and mechanical barriers. Our study indicates that PD-1/PD-L1 expression on CD4(+) T cells may be involved in the pathogenesis of intestinal I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It is involved in programmed cell apoptosis and negatively regulates activated T lymphocytes. It is therefore considered an important cause of immunosuppression [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in programmed cell apoptosis and negatively regulates activated T lymphocytes. It is therefore considered an important cause of immunosuppression [17].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the experiment, the mice were euthanized with an overdose of anaesthetic drugs. The I/R time was set as previously described [19]. Blood samples were obtained by cardiac puncture and were centrifuged at 3000 g for 10 min to separate the serum.…”
Section: Methodsmentioning
confidence: 99%
“…Gut mucosal immunoglobulin (Ig) A is critical for not only defending the host against pathogens but also regulating the host‐commensal relationship . However, we recently demonstrated that intestinal I/R resulted in impaired class switch recombination (CSR) of IgM B + cells, a key biological process involved in mucosal IgA synthesis, in peyer's patches (PPs) and decreased secretory IgA (sIgA) concentration in the gut lumen at 2 hrs after reperfusion . Transforming growth factor (TGF)‐β1, a polypeptide member of the TGF‐β superfamily, plays a pivotal role in cellular proliferation, differentiation and apoptosis as well as mucosal inflammation and immunity .…”
Section: Introductionmentioning
confidence: 99%